2012
DOI: 10.1002/term.1617
|View full text |Cite
|
Sign up to set email alerts
|

Review of vascularised bone tissue-engineering strategies with a focus on co-culture systems

Abstract: Poor angiogenesis within tissue-engineered grafts has been identified as a main challenge limiting the clinical introduction of bone tissue-engineering (BTE) approaches for the repair of large bone defects. Thick BTE grafts often exhibit poor cellular viability particularly at the core, leading to graft failure and lack of integration with host tissues. Various BTE approaches have been explored for improving vascularisation in tissue-engineered constructs and are briefly discussed in this review. Recent invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 201 publications
5
121
0
Order By: Relevance
“…The results are consistent with many preceding studies providing robust scientific evidence on the osteogenic potency of ADSCs and their ability to promote bone repair and regeneration in vivo [40][41][42][43][44]. ADSCs have great potential for bone regeneration due to their many appreciated features, including their increased accessibility and resistance to senescence and malignant transformation [45][46][47].…”
Section: Discussionsupporting
confidence: 91%
“…The results are consistent with many preceding studies providing robust scientific evidence on the osteogenic potency of ADSCs and their ability to promote bone repair and regeneration in vivo [40][41][42][43][44]. ADSCs have great potential for bone regeneration due to their many appreciated features, including their increased accessibility and resistance to senescence and malignant transformation [45][46][47].…”
Section: Discussionsupporting
confidence: 91%
“…This problem is a fundamental challenge for all approaches toward engineering a vascularized bone graft, including those that involve the combination of osteoblasts or mesenchymal stem cells (MSCs) with a separate endothelial cell source. 24 Our prior studies showed that vascular assembly of ASCs is dependent on heterotypic cell-cell interactions, specifically through dense clustering of cells and endogenous plateletderived growth factor (PDGF) signaling. This endogenous behavior is reminiscent of what occurs in native tissues, as proliferating endothelial cells in nascent vessels secrete PDGF-BB to recruit pericytes for vascular maturation and stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Cell-based approaches to vascularized bone tissue engineering also are being pursued. [11][12][13] Numerous studies have shown that coculture of endothelial cells and osteogenic cells allows the formation of both vascular networks and mineralized tissue postimplantation. Kaigler et al implanted poly(lactide-co-glycolide) (PLGA) scaffolds containing a coculture of human microvascular endothelial cells (HMVEC) and bmMSC into immunodeficient mice and monitored ectopic bone formation over 8 weeks.…”
Section: Introductionmentioning
confidence: 99%